Low–lying states of 184W and 184Os nuclei - Sharrad, Fadhil; Okhunov, Abdurahim; Abdullah, Hewa; Abu Kassim, Hasan (IOP Publishing, 2013)
The energy levels, transition energy, B(E2) values, intrinsic quadrupole moment Q0 and potential energy surface for even-even 184W and 184Os nuclei were calculated using IBM-1. The predicted energy levels, transition energy, B(E2) values and intrinsic quadrupole moment Q0 results are reasonably consistent with the experimental data. A contour plot of the potential energy surfaces shows that two interesting nuclei are deformed and have rotational characters.